The Effect of Project-Based Learning on Reading Comprehension Achievement of Junior High School Students - Ariani, Nita (Universitas Katolik Widya Mandala Surabaya, 2023)
This research investigates the effectiveness of project-based learning in enhancing students' understanding abilities in the context of English language learning. Many students face challenges in achieving high levels of proficiency in comprehending written texts. To address this issue, the study explores the impact of project-based learning, which involves authentic tasks, on improving students' overall comprehension skills. Utilizing a quasi-experimental design, the study was conducted with eighth-grade students at a junior high school in Surabaya, East Java. The experimental group received instruction in Collaborative Strategic Reading (CSR), while the control group engaged in Project-Based Learning (PBL). The objective of this investigation was to assess the efficacy of project-based learning in fostering students' comprehension skills through rigorous statistical analysis. The findings reveal a positive influence of project-based learning on students' understanding levels. These results suggest that project-based learning is a recommended approach for teaching language skills, enabling students to enhance their comprehension abilities through engagement in authentic project tasks.